2016
DOI: 10.3389/fmicb.2016.00690
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of Microbial Community of Lake Baikal Bottom Sediments Associated with Gas Discharge to Carry Out the Transformation of Organic Matter under Thermobaric Conditions

Abstract: The ability to compare the composition and metabolic potential of microbial communities inhabiting the subsurface sediment in geographically distinct locations is one of the keys to understanding the evolution and function of the subsurface biosphere. Prospective areas for study of the subsurface biosphere are the sites of hydrocarbon discharges on the bottom of the Lake Baikal rift, where ascending fluxes of gas-saturated fluids and oil from deep layers of bottom sediments seep into near-surface sediment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 83 publications
2
9
0
Order By: Relevance
“…Based on changes in the bacterial content and microflora structure of lake sediments, the relationship between microorganisms and the environment can be shown. Therefore, exploring the bacterial community composition and environmental impact factors in sediments from different geographical locations is of great significance to understand the evolution and function of lake microecological systems and to control eutrophication and control lakes .…”
Section: Introductionmentioning
confidence: 99%
“…Based on changes in the bacterial content and microflora structure of lake sediments, the relationship between microorganisms and the environment can be shown. Therefore, exploring the bacterial community composition and environmental impact factors in sediments from different geographical locations is of great significance to understand the evolution and function of lake microecological systems and to control eutrophication and control lakes .…”
Section: Introductionmentioning
confidence: 99%
“…), which could be transferred to the surface sediments with gas-saturated material from depths of several kilometres (Pavlova et al, 2019a). In cultivated samples of bottom sediments from methane seeps characterized by presence of a fluid convection loop we detected typical mesophilic inhabitants of bottom sediments with a "flexible" metabolism (Bukin et al, 2016;Pavlova et al, 2016). This composition probably allows adapting to the changes in environmental conditions during the burial of individual bottom sediment layers and the circulation of fluid flows.…”
Section: Resultsmentioning
confidence: 78%
“…The experiments have shown that long-term cultivation of microbial communities from bottom sediments of methane seeps Goloustnoye and Posolsk Bank, which were enriched with detritus of the Baikal diatom Synedra acus and CH 4 :H 2 :CO 2 gas mixture, leads to the destruction of algal biomass and formation of petroleum biomarkers, such as retene or gammacerene (Bukin et al, 2016;Pavlova et al, 2016). These data indicate the involvement of microorganisms in the formation of retene during the destruction of diatoms under milder than pyrolysis conditions.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations